Application of the implementation research logic model for evaluating a framework for disseminating arthritis-appropriate evidence-based interventions - Carluzzo, K. L.; Bernstein, L. E.; Chevan, J.; Erck, E.; Murphy, H.; Radske-Suchan, T.; Engebretsen, B.; Schifferdecker, K. E. (Frontiers in Health Services, 2025)
The Public Health Framework for Collaborative Arthritis Management and Wellbeing (“the Framework”) is being piloted as a model to improve health and wellbeing of people with arthritis. This model is built upon a foundational partnership between a clinical entity and a community care hub (“hub”), which recognizes the important role that hubs play in addressing both chronic care needs and unmet social needs of people with arthritis. Specifically, hubs partner with healthcare systems by coordinating and supporting networks of community-based organizations that provide patients with access to health-related resources and services [(such as Arthritis-Appropriate Evidence-Based Interventions (AAEBIs)]. In this Framework, the clinic engages patients in screening (based on physical activity, physical function, and pain), counseling (regarding benefits of physical activity), and referral to community care hubs. At the hub, patients are screened for unmet social needs and are matched with AAEBIs based on a shared-decision-making process. There are two types of AAEBIs: Physical Activity, and Self-Management Education, which may be offered in community-based, clinical, or virtual settings. Through the screening, counseling, and hub referral process, the pilot Framework seeks to increase identification of people who would benefit from AAEBIs, increase AAEBI participation among those who would benefit, and ultimately improve the health and wellbeing of people with arthritis. The evaluation of this Framework leverages an Implementation Research Logic Model (IRLM) and its component frameworks and taxonomies in methods and outcome selection. This study follows the implementation of the Framework through key stages: screening, brief advice and counseling, referral to hub, AAEBI selection and participation, outcomes measurement, and feedback of data to the clinic. This paper offers a practical example of the iterative process we used to make decisions for the evaluation, how the IRLM is used to guide decision-making and analysis, and the methods of our evaluation plan.